Effect of Ag addition on the martensitic phase of the Cu-10 wt.% Al alloy - Silva, R.A.G. (2007)
Thermal analysis and compression tests at room temperature have been carried out for Cu-10 wt.% Al and Cu-10 wt.% Al-10 wt.% Ag alloys samples. The results indicate that the decomposition reaction of the (β1) parent phase is decreased suppressed and a martensite stabilization effect can be induced by Ag addition. The Cu-Al-Ag alloy shows some degree of shape memory capacity.